A Study of Job Demands Resources as Antecedents of Educators Engagement in Universities - Rony Setiawan; Kezia Kurniawati Nursalin; Ariesya Aprillia (Pandawan, 2026)
The performance of educational institutions is closely linked to the quality of lecturers’ work, which is largely influenced by their professionalism and work attitudes, particularly job engagement. High levels of job engagement encourage lecturers to contribute actively and demonstrate sustained dedication in their roles. Drawing on empirical evidence, this study examines the effects of Job Demands (JD) and Job Resources (JR) on lecturers’ Job Engagement (JE), while also exploring the moderating role of personal characteristics. This study adopts a quantitative approach using regression analysis and a univariate General Linear Model (GLM) to test both direct and interaction effects. The findings, based on data collected from 41 lecturers at a private university in Bandung, indicate that job demands negatively affect job engagement, whereas job resources have a positive effect. Furthermore, personal characteristics such as tenure, side job ownership, and cognitive style dimensions (information seeking and worldview) significantly influence the relationship between JD, JR, and JE. These results suggest that the dynamics of the Job Demands–Resources (JD-R) model are not universal but vary according to career stage and individual cognitive preferences. Practically, the study highlights the importance of adopting adaptive and individualised management strategies in balancing job demands and enhancing job resources to sustain lecturers’ engagement and academic performance in higher education contexts.